2nd generation IIUM buggy car – Part I: design - Mohiuddin, A. K. M. (IIUM Press, 2011)
This chapter provides the detailed information involved in the design of the Second generation InJM buggy car project. Part I includes all details regarding the method of design, design's philosophy, concept and model construction and result evaluation. Background research and literature review have been done in order to provide a basic reference for this buggy car design. Correct material selections and its dimensions can reduce the overall weight of the car while accurate design collaboration within the suspension system can ensure a better maneuver characteristic. A number of design options have been generated. The best choice was based on a lightweight buggy car with high strength performance, good handling characteristic, and also considering excellent driver's ergonomic aspect